Implementation of Social and Environmental Accounting as Corporate Social Responsibility in Indonesia - Wahyuni; Amira Fauziah; Rusmiati; Dwi Nur Isra; Safaruddin (Pustaka Digital Indonesia, 2024)
This research explores the implementation of social and environmental accounting as a form of corporate social responsibility in Indonesia. Companies today are not only required to present financial reports, but also have to consider the social and environmental impacts of their operations. This research uses a literature study approach to collect data from various sources relevant to the topic of corporate social responsibility (CSR) and social accounting. The research results show that social and environmental accounting plays a crucial role in reporting corporate accountability to society and the environment. Through social accounting, companies can demonstrate their commitment to social responsibility, report social impacts, and meet stakeholder expectations. The application of social and environmental accounting also helps companies manage environmental and social risks, as well as increasing transparency and reputation. This research suggests that companies need to integrate social accounting in their reports to ensure transparent and accountable reporting. This is important to build public trust and fulfill legal obligations in accordance with applicable regulations. By adopting this approach, companies can not only increase their social responsibility but also support long-term environmental and social sustainability.